Criminal Implementation of Cyberbullying Based on Electronic Information and Transaction Law and Islamic Law - Inayah, Jastin Nurul; Nugroho, Taufiq (JURNAL USM LAW REVIEW, 2024)
This writing aims to determine the application of the law against cyberbullying based on Article 27 of Law No. 19 of 2016 concerning amendments to Law No. 11 of 2008 on Electronic Information and Transactions. This research is able to provide a more comprehensive understanding, which focuses on the application of the principle of justice that will be applied by law enforcement officials and the perspective of Islamic law on cyberbullying criminal acts. The method used is normative juridical with a statutory approach. The urgency of writing this legal article is a comprehensive analysis of the implementation of article 27 of Law no.19 of 2016 which more specifically discusses the act of cyberbullying and the view of Islamic law regarding the act of cyberbullying. The results of this study are to determine the application of article 27 of Law no.19 of 2016 to acts of cyberbullying, if the perpetrator who commits acts that are included in the classification of cyberbullying acts including Flaming, Harrasment, Denigration, and Outing, the perpetrator can be charged with Article 27 paragraph (3) of the ITE Law jo. Article 45 paragraph (3) of the ITE Law, with a maximum imprisonment of 4 years or a maximum fine of Rp750,000,000.00. To find out the view of Islamic law on cyberbullying which is analyzed to find out the consequences and sanctions according to Islamic law.